Encyclopedia of sports management and marketing - Swayne, Linda E.; Dodds, Mark. (Thousand Oaks, Calif. : Sage Publications, Inc, 2011)
'This four-volume set introduces, on the management side, principles and procedures of economics, budgeting and finance; leadership; governance; communication; business law and ethics; and human resources practices; all in the sports context. On the marketing side this reference resource explores two broad streams: marketing of sport and of sport-related products (promoting a particular team or selling team- and sport-related merchandise, for example), and using sports as a platform for marketing non-sports products, such as celebrity endorsements of a particular brand of watch or the corporate sponsorship of a tennis tournament. Together, these four volumes offer a comprehensive and authoritative overview of the state of sports management and marketing today, providing an invaluable print or online resource for student researchers'--
v. 1. A-E -- v. 2. E-M -- v. 3. N-S -- v. 4. S-Z, Index.
Includes bibliographical references and index.
Keywords: Sports -- Management -- Encyclopedias; Sports administration -- Encyclopedias; Sports -- Marketing -- Encyclopedias